Edukasi Lingkungan Bersih dan Pelatihan Pembuatan Tong Sampah Berbahan Limbah Plastik Bagi Santri TPQ Se Desa Sukoharjo Kediri - Nurjannah, Fitrotun (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
Islam is very concerned about cleanliness so that a Muslim should keep himself, his clothes, and his environment clean. In reality, cleanliness is still a problem that we need to pay attention to. The research approach used in this research is the PAR or Participatory Action Research method. Participatory Action Research (PAR) is a qualitative approach that integrates methods and techniques of observing, documenting, analyzing and interpreting the characteristics, patterns, attributes and meanings of the human phenomenon under study. PAR is a collaborative process between research, education and action, including in Islamic Education Institutions, one of which is TPQ which will be used as a research site is TPQ Shirotul Jannah which is located in the hamlet of Puhrejo Sukoharjo village, Kayen Kidul sub-district. Based on the researcher's experience, there is still a lot of garbage scattered in the yard, and the recitation room is dirty and dusty. Based on this, we held a "Clean Environment Education and Training on Making Plastic Waste-Based Trash Bins for Santri Tpq Se Sukoharjo Kediri Village." on August 10, 2023 at TPQ Shirotul Jannah Puhrejo brought a little impact of change, namely the availability of trash bins, awareness of TPQ students about maintaining cleanliness as well as throwing garbage in its place increased and there were slogans about maintaining cleanliness in the TPQ environment.